WACANA POLITIK NICOLAS SARKOZY: ANALISIS PSIKOSTRUKTURAL LACANIAN - Aprillia Firmonasari (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2007)
The article attempts to analyze Nicolas Sarkozy’s political discourse in the 2007 French Presidential Election. His political campaign ended up in victory and he was later voted the President of France. The analysis adopts Lacanian psycho-structural analysis because it enables the writer to uncover which type of passion Sarkozy promoted in his political discourse. In the efforts to gain vote, Sarkozy’s political discourse was set to be persuasive and provocative in nature raising the issue of passive narcissist passion. This issue was accomplished through the use of signs, metonymies, and metaphors.